Chemoenzymatic Synthesis of Enantioenriched (R)‐ and (S)‐Aryloxyalkanoic Herbicides. Issue 25 (1st July 2022) - Colombo, Danilo; Albergati, Alessia; Ferrandi, Erica E.; Tessaro, Davide; Gatti, Francesco G.; Brenna, Elisabetta; Monti, Daniela; Parmeggiani, Fabio
Abstract: The combination of a biocatalytic asymmetric C=C reduction with a simple sequence of chemical transformations was implemented in a new chemoenzymatic synthesis of various substituted aryloxyalkanoic acids, used as weed‐killing agrochemicals or chiral precursors. By careful selection of the biocatalyst, either enantiomer of the product could be obtained in good yield and moderate to good ee. The method relies on the use of simple and commercially available starting materials, and requires neither purified enzymes nor chromatographic separations. Abstract : A versatile and sustainable approach to one of the most commonly employed families of herbicides has been developed, which is based on a biocatalytic reductive dehalogenation followed by simple chemical manipulations. A range of commercially relevant target molecules have been obtained in good yield and moderate to excellent enantioselectivity (to either enantiomer), without chromatographic purifications and by using crude enzyme preparations.